Analysis of 307 cases with drug‐induced liver injury between 2010 and 2018 in Japan. Issue 1 (15th January 2019) - Aiso, Mitsuhiko; Takikawa, Hajime; Tsuji, Keiji; Kagawa, Tatehiro; Watanabe, Masaaki; Tanaka, Atsushi; Sato, Ken; Sakisaka, Shotaro; Hiasa, Yoichi; Takei, Yoshiyuki; Ohira, Hiromasa; Ayada, Minoru; et al.
Abstract : Aim: In order to know the present status of drug‐induced liver injury (DILI) in Japan, we present the data of prospectively collected DILI cases between 2010 and 2018 from 27 hospitals. Methods: Drug‐induced liver injury cases diagnosed by DILI experts from 27 hospitals all over Japan have been prospectively collected since 2010. Alanine aminotransferase level ≥150 U/L and/or alkaline phosphatase ≥2× upper limit of normal were inclusion criteria. Results: In total, data of 307 cases (125 male and 182 female individuals) aged between 17 and 86 years old were collected. The types of liver injury were as follows: 64% hepatocellular type, 20% mixed type, and 16% cholestatic type. A drug‐induced lymphocyte stimulation test was carried out in 59% of cases, and was positive in 48% and semipositive in 3% of cases. Eosinophilia ≥6% was observed in 27% of cases. Fifty‐three percent of DILI cases occurred within 30 days and 79% of DILI cases occurred within 90 days after starting drug administration. By the diagnostic scale of the Digestive Disease Week (DDW)‐Japan 2004 workshop, 93.8% of cases were diagnosed as "highly probable", and 5.9% as "possible". Conclusions: Japanese DILI patients are somewhat different from those of Europe and North America. The diagnostic scale of the DDW‐Japan 2004 workshop has been used in Japan. However, there are many issues to improve the causality assessment of DILI that we must investigate in the future. It is critical to elucidate the mechanisms of drug metabolism and the pathophysiology of liver injury by various drugs to prevent DILI.